2007
DOI: 10.1080/15459620701540618
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Spatial Variability of Personal Sampler Inlet Locations

Abstract: This article examines the spatial variability of dust concentrations within a coal miner's breathing zone and the impact of sampling location at the cap lamp, nose, and lapel. Tests were conducted in the National Institute for Safety and Health Pittsburgh Research Laboratory full-scale, continuous miner gallery using three prototype personal dust monitors (PDM). The dust masses detected by the PDMs were used to calculate the percentage difference of dust mass between the cap lamp and the nose and between the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In fact, spatial variability can lead to measurement biases of over 20%. (25,26) Therefore, in this study, the Airtec and NIOSH method 5040 results were compared using a method that takes spatial variability into account. The bias between the Airtec and NIOSH method 5040 and the percent difference between duplicate NIOSH method 5040 samples (randomly chosen from the triplicate samples) were compared.…”
Section: Comparison To Niosh Methods 5040mentioning
confidence: 99%
“…In fact, spatial variability can lead to measurement biases of over 20%. (25,26) Therefore, in this study, the Airtec and NIOSH method 5040 results were compared using a method that takes spatial variability into account. The bias between the Airtec and NIOSH method 5040 and the percent difference between duplicate NIOSH method 5040 samples (randomly chosen from the triplicate samples) were compared.…”
Section: Comparison To Niosh Methods 5040mentioning
confidence: 99%
“…The term "calm" used throughout this paper refers to a condition without external wind as compared to the previous field and wind tunnel studies [2][3][4][5][6] . Ethanol was used as a representative organic solvent.…”
Section: Short Communicationmentioning
confidence: 99%
“…However, some doubts have been raised about this assumption. Several studies have mentioned that the concentration in the breathing zone can vary when the worker is close to the contaminant source [2][3][4][5][6] . Bull et al 2) showed that test aerosol concentrations at the upper parts of the body tend to be higher than the concentrations at the lower parts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When quartz particles are present in the coal dust, additional restrictions are applied (McPherson, 1993;Vinson et al, 2007).…”
Section: Cfd Modelling Of Dust Behaviourmentioning
confidence: 99%